Current treatment options for nonalcoholic fatty liver disease. Issue 3 (May 2019) - Shetty, Akshay; Syn, Wing-Kin
Abstract : Purpose of review: Nonalcoholic fatty liver disease (NAFLD) is the leading cause of liver disease in the United States and is strongly associated to the metabolic syndrome. In this review, we will discuss the evidence behind the current recommendations on lifestyle modifications and available treatment options for NAFLD. Recent findings: The unrelenting rise in obesity and diabetes epidemic has led to a large healthcare burden from NAFLD and it is projected to continue to grow over the next two decades. Lifestyle modification that leads to weight loss is effective at treating NAFLD, but these modifications require a multidisciplinary approach for success in the real world. Multiple pharmacologic treatment options have been studied with promising results, but none have been approved for treatment in the United States. Clinical trials are on-going to study further pharmacologic treatment alternatives. Summary: NAFLD is the most common chronic liver disease in United States, and an independent risk factor for mortality. Implementation of lifestyle modifications through a multidisciplinary approach and careful selection of patients for pharmacologic interventions will be essential for successful management of NAFLD.